The preservation and standardisation of South African hides and skins - Kritzinger, Carl Cronje (Rhodes University, Faculty of Commerce, Department of Economics, 1946)
During the past fifty years the problems of the leather industry have been tackled from various aspects by scientific research workers all over the world, and "works control" today forms one of .the important foundation stones of efficiently run tanneries and footwear factories. The raw materials of the tanning industry, hides and skins, constitute the largest proportion of the cost of production, and it is ' only natural that the improvement of these valuable raw materials should be given primary attention by any leather scientist. Until only a few years ago, however, the South African hide and skin industry was at a serious Â·disadvantage in that it had to base recommendations for improved production methods almost exclusively on overseas experience and practice. The importance of the differences existing between South Africa and European or American countries with regard to climate, slaughtering, hide and skin production in general, transport and sale, however, necessitates a different approach to our specific problems. The overseas hide and skin industry has had, since the beginning of this century, the support and particularly the guidance of scientific research; but it was not until 1935, when, through the support of the Hide and Skin advisory Board, Prof. W. F. Barker founded the original Tanning, Hides and Skins Research Department at Rhodes University College, Grahamstown, that science actively entered the field of hide and skin production in this country. Much of the work done had of course to be based on the results obtained by overseas research institutions, and the adaptation of such results to suit our own problems for some time formed a considerable part of the investigations undertaken. This thesis embodies the results of work undertaken by the writer since 1943 on specific problems of the South African hide and skin industry. Much of the work has already received publication through the Circulars and Journals of this Institute, but it is embodied here again in order to maintain the continuity. The attitude throughout has been to evolve methods of production suited to our own conditions, and the adoption of the recommendations contained in this thesis should lead to improvement in the quality of our hides and skins. Much still remains to be done, and it is the sincere hope of the writer that this work will stimulate and form the basis for subsequent investigations. For that reason more or less detailed descriptions are given of all experiments conducted, and the theory of curing in its relation to tanning is briefly discussed . The literature in each of the four Parts has been attached at the end of that Part to facilitate reference work. At the same time, however, the writer kept in mind the requirements of the trade itself, therefore much of the work is discussed in popular terms. It is hoped that the correct balance between the two extremes has been arrived at.
Keywords: Uncatalogued